THE RELATIONSHIP BETWEEN SCHOOL LEADERSHIP AND JOB SATISFACTION OF SECONDARY SCHOOL TEACHERS: A MEDIATING ROLE OF TEACHER EMPOWERMENT - Yangaiya, Salisu Abba; Magaji, Kabir (PEOPLE: International Journal of Social Sciences, 2015)
The purpose of this study is to examine the influence of School leadership (SL) on teachers’ Job Satisfaction (JB), using Teachers’ Empowerment (TE) as mediating variable. Data was collected from 370 secondary school teachers in Katsina state Nigeria. The data was collected using questionnaires adopted and adapted from Devis (2009), Hackman and Oldhan (1975) and Menon (2001) for School leadership, Job Satisfaction and Teachers’ Empowerment respectively. Statistical Package for Social Science Research (SPSS) version 20.0 and AMOS (version 16.0) were used to analyze the data collected. Findings indicate that School Leadership influences teachers’ Job Satisfaction (JB) (Standardize coefficient .06). Moreover, Teachers’ Empowerment influences Job Satisfaction (Standardized coefficient .72). Additionally, Teachers’ Empowerment (TE) strongly mediates the relationship between School Leadership and teachers’ Job Satisfaction (standardize coefficient 0.51) The practical implication of this study is that education stakeholders i.e. ministry of education officials, zonal offices officials, principals among others should provide a conducive atmosphere for teachers to be empowered to enable them exhibits Job Satisfaction. The study is important because before now very few studies were conducted on School Leadership and Job Satisfaction in Nigeria in general and Katsina state in particular.